Spot Loves Sport - Hill,Eric (London Penguin Random House, 2012)
"Spot Loves Sport" by Eric Hill is a delightful children's book featuring Spot, the beloved puppy character. In this story, Spot explores various sports, showcasing his enthusiasm and energy. He engages in different activities, like playing soccer, swimming, and running, highlighting the fun and excitement of sports. Throughout the book, young readers are introduced to basic concepts of teamwork, friendship, and the joy of physical activity. The colorful illustrations and simple text make it accessible for toddlers and preschoolers, encouraging them to get active and enjoy sports themselves. Overall, it$1 (Bs a charming read that promotes a healthy, active lifestyle.s
Keywords: English Story book